Pharmaceutical distribution networks in China: analysis of benefits and challenges of entering the Chinese market - Wegner, Jennifer (2015)
Entering foreign markets is aligned with objectives related to and influenced by the market entered. Operationalisation of objectives as well as the given environment of the host country influence setup of distribution activities which demands for joint analysis of both topics.